Del individuo aislado a la comunidad cohesionada. Los límites a la libertad en Rawls y Aron (2009)
The theoretical development of John Rawls and Raymond Aron highlights a liberalism that acknowledges as its starting point the individual being free and isolated, which, because of the influence of internal and external constraints on individual liberties, encourages the construction of a cohesive political community. With such a perspective challenges the modern version of liberty as an absence of coercion and, at the same time, highlights the validity of the discussion about the limits of liberty in contemporary societies. This phenomenon can be described as the transition from liberalism to social democracy, or as revision of the negative conception of individual liberties.